Bimetallic nanoparticles as cascade sensitizing amplifiers for low-dose and robust cancer radio-immunotherapy - Yupeng Wang; Lina Wang; Tao Li; Min Ouyang; Hejian Xiong; Dongfang Zhou (Acta Pharmaceutica Sinica B, 2024)
Radiotherapy (RT) is one of the most feasible and routinely used therapeutic modalities for treating malignant tumors. In particular, immune responses triggered by RT, known as radio-immunotherapy, can partially inhibit the growth of distantly spreading tumors and recurrent tumors. However, the safety and efficacy of radio-immunotherapy is impeded by the radio-resistance and poor immunogenicity of tumor. Herein, we report oxaliplatin (IV)-iron bimetallic nanoparticles (OXA/Fe NPs) as cascade sensitizing amplifiers for low-dose and robust radio-immunotherapy. The OXA/Fe NPs exhibit tumor-specific accumulation and activation of OXA (II) and Fe2+ in response to the reductive and acidic microenvironment within tumor cells. The cascade reactions of the released metallic drugs can sensitize RT by inducing DNA damage, increasing ROS and O2 levels, and amplifying the immunogenic cell death (ICD) effect after RT to facilitate potent immune activation. As a result, OXA/Fe NPs-based low-dose RT triggered a robust immune response and inhibited the distant and metastatic tumors effectively by a strong abscopal effect. Moreover, a long-term immunological memory effect to protect mice from tumor rechallenging is observed. Overall, the bimetallic NPs-based cascade sensitizing amplifier system offers an efficient radio-immunotherapy regimen that addresses the key challenges.